Outcome-Based Comparison of Patients with Myocardial Infarction with and Without Respiratory Tract Infections - Choudhary, Hira; Zamir, Muhammad Usama; Malik, Muhammad Imtiaz (Biological and Clinical Sciences Research Journal, 2025)
Myocardial infarction (MI) remains a leading cause of morbidity and mortality globally. Coexisting systemic conditions such as respiratory tract infections (RTIs) may worsen clinical outcomes due to heightened inflammatory and metabolic stress. Objective: To compare in-hospital outcomes of patients with MI in the presence and absence of concurrent respiratory tract infections. Methods: This comparative cross-sectional study was conducted at Fauji Foundation Hospital, Lahore from 10 August 2024 to 15 March 2025. A total of 455 patients admitted with a confirmed diagnosis of MI were enrolled over the study period using a non-probability consecutive sampling technique. All patients aged 18 years and above who were diagnosed with ST-elevation myocardial infarction (STEMI) or non-ST-elevation myocardial infarction (NSTEMI), based on clinical presentation, electrocardiographic findings, and elevated cardiac biomarkers (troponin I/T or CK-MB), were eligible for inclusion. Results: Patients with RTIs were older and had higher rates of diabetes and hypertension (p < 0.05). In-hospital mortality was significantly higher in the RTI group (16.1% vs. 7.3%, p = 0.006), with longer hospital stays (7.4 ± 2.6 vs. 5.6 ± 2.1 days, p < 0.001), greater ICU admissions (32.1% vs. 14.6%, p < 0.001), and more frequent mechanical ventilation (19.6% vs. 6.1%, p < 0.001). RTI patients also had increased incidence of acute heart failure (29.5% vs. 17.2%, p = 0.004) and arrhythmias (22.3% vs. 13.1%, p = 0.01). On multivariate analysis, RTI was an independent predictor of in-hospital mortality (AOR: 2.38; 95% CI: 1.25–4.51) and ICU admission (AOR: 2.91; 95% CI: 1.73–4.91). Conclusion: It is concluded that concurrent respiratory tract infections in patients with myocardial infarction are associated with significantly poorer in-hospital outcomes. These findings emphasize the importance of early recognition, aggressive management, and possibly preventive strategies such as vaccination in MI patients at risk of infection.